2016 IEEE International Conference on Serious Games and Applications for Health (SeGAH) 2016
DOI: 10.1109/segah.2016.7586282
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation with cognitively-impaired older adults of attention management in the Embodied Conversational Agent Louise

Abstract: We present the first experiment we conducted to evaluate the attention monitoring performance of Louise, following a Wizard of Oz method, during the interactions with a cohort of 8 elderly users in a day hospital environment. Louise is a new, semi-automatic prototype of an Embodied Conversational Agent (ECA), a virtual character interacting with users through social-like communication, adapted to the special needs of older adults with cognitive impairment; it is intended to ultimately provide assistance in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
4
8
0
Order By: Relevance
“…The first issue we observed is that some of the test participants tended to forget that they could only answer by "yes" or "no" and answered incorrectly, particularly the participants with the most severe memory impairment, scoring less than 20/30 at the MMSE, who account for 29 of the 56 incorrect answers (52%). This confirms the observations revealed in the anthropological analysis we conducted in the first round of experiments, reported in [41], that people with cognitive impairment tend to provide more elaborate answers and interact in a "social" way. Given this result, our error management strategy that lists the possible answers proved useful, as participants could correct their mistakes in all cases, especially after the system was changed for the valid answer reminder to be performed after two errors instead of three.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The first issue we observed is that some of the test participants tended to forget that they could only answer by "yes" or "no" and answered incorrectly, particularly the participants with the most severe memory impairment, scoring less than 20/30 at the MMSE, who account for 29 of the 56 incorrect answers (52%). This confirms the observations revealed in the anthropological analysis we conducted in the first round of experiments, reported in [41], that people with cognitive impairment tend to provide more elaborate answers and interact in a "social" way. Given this result, our error management strategy that lists the possible answers proved useful, as participants could correct their mistakes in all cases, especially after the system was changed for the valid answer reminder to be performed after two errors instead of three.…”
Section: Resultssupporting
confidence: 91%
“…Our interaction manager could very well handle open questions with multiple possible answers, though choosing the appropriate response could be challenging and would likely require some language processing of the user's answers, to interpret his or her intents, in the behavior analysis stage. However, with our target user group, we have identified that narrow or contrasted questions, such as yes/no questions, should be privileged [41]. This is also in line with the recommendations of Zajicek [44], who suggested that menus in speech-based interfaces for older adults should be limited to 3 items at a time.…”
Section: Asking Questions and Reacting To Answerssupporting
confidence: 83%
See 2 more Smart Citations
“…Therefore, there is reason to assume that a conversational application considering the notions of content packaging by means of the relation between thematicity and prosody will benefit from the same advantages as in natural conversation environments. Most of all, conversational avatars in applications for children in educational settings [16], applications for those with special needs [1] as well as for elderly [2] and, in particular, for those with cognitive impairments [17], would greatly benefit from such a communicatively-oriented improvement.…”
Section: Motivation and Backgroundmentioning
confidence: 99%